CAF-induced placental growth factor facilitates neoangiogenesis in hepatocellular carcinoma. (11th December 2019) - Liu, Zhongjian; Chen, Mingmei; Zhao, Rongce; Huang, Yuan; Liu, Fei; Li, Bo; Qin, Yang
Abstract: As a highly malignant tumor, hepatocellular carcinoma (HCC) is the third leading cause of cancer-related deaths worldwide. In most HCC patients, the development of HCC begins with hepatitis, which is followed by fibrosis and cirrhosis before progressing to HCC. Cancer-associated fibroblasts (CAFs), which are generally believed to be derived from activated hepatic stellate cells (HSCs), are highly involved in the development of HCC through the secretion of cytokines and angiogenic factors. The results of our study showed that a considerable number of CAFs highly expressed CD90 and were enriched in HCC tissues. Bioinformatics analysis of the transcriptome of HCC tissues revealed that placental growth factor (PlGF) is significantly correlated with CD90 expression. The isolated primary CAFs and activated HSCs overexpressed PlGF and CD90. In addition, the results of gene expression profiling interactive analysis based on The Cancer Genome Atlas showed that high levels of both PlGF and CD90 are correlated with tumor angiogenesis markers (CD31, CD34, and CD105) and predict poor HCC patient prognosis. In summary, our results suggest that CAFs can generate PlGF and may provide an effective target for CAFs-regulated neoangiogenesis in HCC.